A streamlined framework for calculating the response of steel-supported bridges to open-air tanker truck fires. (April 2015) - Quiel, Spencer E.; Yokoyama, Takayuki; Bregman, Lynne S.; Mueller, Kevin A.; Marjanishvili, Shalva M.
Abstract: Several recent fire-induced bridge failures have highlighted the need for improved simplified tools to evaluate the response of bridges to fire. A streamlined design framework is proposed for efficient calculation of a steel-supported bridge's response to an open-air hydrocarbon pool fire resulting from a tanker truck crash and subsequent fuel spill. The framework consists of four steps: (1) calculate the fire's characteristics and geometry; (2) calculate the heat transfer from the fire to the structural elements; (3) calculate the temperature increase of the structural elements; and (4) calculate the resulting material and mechanical response of the structural elements. The approach, which uses a modified discretized solid flame model to represent the pool fire, synthesizes calculation techniques based on both first principles and empirical data to quantify the extent of damage caused by the fire hazard. Due to its efficiency, this approach can be used to calculate an envelope of effects for a wide range of fire parameters. The framework is applied to a case study of the 2007 fire event and collapse of an overpass bridge at the MacArthur Maze freeway interchange near Oakland, CA, USA. The framework is then demonstrated as a design tool to determine the extent of the overpass' vulnerability to a similar fire along the freeway below. Graphical abstract: Highlights: Proposed framework calculates bridge response to open-air tanker truck fires. Approach accounts for the intensity, duration and orientation of fire to the bridge. A modified discretized solid flame model is used to calculate radiation heat flux. The framework is successfully used for a case study of a recent bridge fire event. Approach is computationally efficient for parametric studies of bridge fires.